Especificidades do uso do inglês (LE) na área técnica empresarial : a relação entre necessidades, planejamento de curso e material didático - Lopes, Jaqueline (2008)
This study presents a comparison of the English as a Foreign Language courses offered at two companies. Our purpose is to evaluate what is the treatment of the language use specificities in these companies employees peformance of their functions in their daily work routine. We discuss the key role of needs analysis in the design of effective LSP courses, as stated by Hutchinson and Waters (1984, 1987) and Dudley-Evans and St John (1998), among other reserchers in the field. Our data analysis shows how important it is that professionals who decide to work in this area search for solid theoretical information on this fruitful and progressive branch of EFL/ESL, more specifically. Our study can provide initial theoretical basis for those language teachers, especially the ones working with EFL,who wish to be introduced or to obtain